Effectiveness of multidisciplinary primary prevention in decreasing the risk of work disability in a low-risk population - Saltychev, Mikhail; Laimi, Katri; El-Metwally, Ashraf; Oksanen, Tuula; Pentti, Jaana; Virtanen, Marianna; Kivimäki, Mika; Vahtera, Jussi (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'The aim of this study was to evaluate the effectiveness of a 4-week primary prevention program (vocationally oriented multidisciplinary early rehabilitation or VOMR) in reducing the risk of long-term work disability among public sector employees at risk of deteriorating work capacity because of work-related strain. ' ' METHODS ': 'As a part of the prospective Finnish public sector study, a follow-up study was carried out among 1394 public sector employees who underwent VOMR and their 4146 propensity score-matched controls. Baseline characteristics of 41 488 employees with full data on all 25 matching variables, measured from survey responses and national health registers, were used to calculate a propensity score for each employee to be granted rehabilitation. The cases were compared with the controls using Cox proportional hazard models as regards the risk of long-term work disability (sick leave >90 days or retirement on health grounds) after rehabilitation. ' ' RESULTS ': 'During a mean follow-up of 2.8 years [standard deviation (SD) 1.49, range 0.04–5.0], incident all-cause work disability was observed for 6.1% of the rehabilitants and 6.2% of the controls [hazard ratio (HR) 0.98, 95% confidence interval (95% CI) 0.76–1.25]. The corresponding HR for the main causes of work disability stemming from musculoskeletal diseases and mental disorders were 0.86 (95% CI 0.57–1.30) and 1.08 (95% CI 0.67–1.74), respectively. ' ' CONCLUSIONS ': 'VOMR was not associated with a lowered risk of long-term work disability compared to the controls. No support was obtained for the effectiveness of primary prevention for work disability in a low-risk cohort of employees.
Keywords: disability pension; early rehabilitation; low-risk population; multidisciplinary primary prevention; prevention; propensity score; rehabilitation; retirement; vocational rehabilitation; work disability